Ag2Cu3Cr2O8(OH)4: a new bidimensional silver–copper mixed-oxyhydroxide with in-plane ferromagnetic coupling. Issue 4 (3rd January 2017) - Casañ-Pastor, Nieves; Rius, Jordi; Vallcorba, Oriol; Peral, Inma; Oró-Solé, Judith; Cook, Daniel S.; Walton, Richard I.; García, Alberto; Muñoz-Rojas, David
Abstract : A new brucitic Ag–Cu–Cr mixed oxide with bidimensional ferromagnetic coupling is obtained by soft hydrothermal methods. Abstract : Ag2 Cu3 Cr2 O8 (OH)4, a new Ag–Cu–Cr–O layered mixed oxide, prepared by soft hydrothermal heterogeneous reactions, is reported. The new phase is an oxyhydroxide and presents a structure with alternating brucite-like Cu–O and Ag–O layers connected by individual chromate groups. The crystallographic structure has been solved and refined from high resolution powder X-ray diffraction data and is supported by density functional theory calculations, yielding a triclinic, space group P 1̄, a = 5.3329(1) Å, b = 5.3871(1) Å, c = 10.0735(1) Å, α = 80.476(1)°, β = 87.020(1)°, γ = 62.383(1)°. Bond valence sums suggest the formulation of Ag + 2 Cu 2+ 3 Cr 6+ 2 O8 (OH)4, an electronic state fully supported by X-ray photoelectron spectroscopy (XPS) and Cr K-edge X-ray absorption near edge structure (XANES) measurements. Ag2 Cu3 Cr2 O8 (OH)4 exhibits bidimensional Cu–O–Cu ferromagnetic correlations that are apparent at much higher temperatures than in other similar Cu–O layered structures, without coupling between Cu–O layers, which represents a unique case in the recent family of silver copper oxides. The role of Ag inducing bidimensionality in copper oxides is therefore expanded further with the presence of chromate anions. Ab initio calculations using density functional theory show that the electronic states involved originate mainly from Cu and OH orbitals, with minor contributions from Cr and the O atoms linking the Cr tetrahedra to the brucitic Cu–O layer, and almost no contribution from Ag. Further modeling of the in-plane magnetic interactions between Cu atoms suggests that the coupled magnetized stripes are responsible for the observed behavior. The results are discussed in relation with previous Ag–Cu mixed oxide phases where metallic behavior or ferro–antiferro transitions had been observed. The structure of this new Ag–Cu–O phase as compared with previous silver copper oxides supports the conclusion that the Ag–Cu layered ordering is favored under oxidizing conditions.